Symptoms associated with inflammatory arthritis are common in the primary care population: results from the joint symptoms survey. (11th May 2019) - Hider, Samantha L; Muller, Sara; Helliwell, Toby; Prior, James A; Scott, Ian; Lawton, Sarah A; Zwierska, Irena; van Schaardenburg, Dirkjan; van der Helm-van Mil, Annette; Raza, Karim; Mallen, Christian D
Abstract: Objectives: To describe the prevalence of self-reported inflammatory joint symptoms, such as joint pain, stiffness and swelling, in UK primary care patients consulting for both musculoskeletal (MSK) and non-musculoskeletal (non-MSK) complaints. Methods: A joint symptoms questionnaire survey was sent to 10 161 individuals, of whom 5050 had consulted for MSK problems. These were matched by age, gender and general practice to non-MSK consulters. Participants provided data on relevant symptoms such as joint pain, stiffness and swelling. The prevalence of these symptoms, their severity and impact were compared between MSK and non-MSK consulters. Results: A total of 4549 adults responded to the survey (adjusted response 45.8%) of whom 52.3% consulted for a MSK problem. The mean (s .d .) age was 61.6 (14.8) years and 58.9% were female. Persistent (on at least half of the days in the last month) inflammatory symptoms were common even in non-MSK consulters, with 42% reporting joint pain, 36% reporting joint stiffness and 18% reporting joint swelling. This is in comparison with 62% reporting joint pain, 50% stiffness and 24% swelling among MSK consulters. Conclusions: Although symptoms such as persistent joint pain, swelling and stiffness are predictive of inflammatory arthritis, large numbers of people consulting primary care for non-MSK reasons report these symptoms when asked by questionnaire. This compounds the challenges of diagnosing inflammatory arthritis in a non-specialist setting where new approaches are needed to ensure accurate, early diagnosis, facilitating a treat-to-target approach.